2017
DOI: 10.12968/jowc.2017.26.3.121
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of blood cells and inflammatory factors in wounds

Abstract: Our findings suggest that the combination of the markers, percentage of neutrophils and monocytes, platelets, CRP and IgG levels could be useful prognostic indicators of the inflammatory phase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Vacuum, drainage, or other external devices were used in 124 of the 280 (44%) studies and thus were the most frequently used methods of sample collection 22–27,29–146 ; the vast majority of sample collections using this method (75%, 103/138), were from surgical wounds (Figure 2B). Three other frequently used methods were extraction from absorbent material (31%, 86/280),…”
Section: Resultsmentioning
confidence: 99%
“…Vacuum, drainage, or other external devices were used in 124 of the 280 (44%) studies and thus were the most frequently used methods of sample collection 22–27,29–146 ; the vast majority of sample collections using this method (75%, 103/138), were from surgical wounds (Figure 2B). Three other frequently used methods were extraction from absorbent material (31%, 86/280),…”
Section: Resultsmentioning
confidence: 99%
“…CRP concentration <8 mg/L is considered a normal clinical condition in wounds [ 27 ], whereas higher values can be used to discriminate different critical conditions. Cerveró-Ferragut et al reported that proliferative and inflammatory phases had an average CRP level equal to 90 mg/L, which dropped to 5.2 mg/L in the maturation phase [ 131 ]. An average CRP level of about 66 mg/L was reported for trauma-related chronic wounds [ 132 ], whereas wound infections following surgically managed fractures were associated with a CRP concentration of 141 mg/L [ 133 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the proliferation phase includes broplasia and matrix formation, which is extremely important in the formation of granulation tissue. The formation of granulation tissue depends on the broblast, a critical cell in matrix formation [13]. Far from being just a collagen producer, broblasts produce elastin, bronectin, glycosaminoglycan, and proteases, which are responsible for physiological debridement and remodeling [14].…”
Section: Introductionmentioning
confidence: 99%